A multi-biomarker assessment of single and combined effects of oxytetracycline and ciprofloxacin on Mytilus spp - Vieira, Madalena Filipa Moreira (2024)
Antibiotics are a class of drugs widely used throughout the world to treat infections in both humans and animals. Due to their widespread use, these drugs are eventually released into the environment, as wastewater treatment plants are not efficient in eliminating them. This causes these compounds to be widely distributed in aquatic environments, justifying concerns about the impact they may have on the species present there. Thus, this work aims to characterize the toxicity arising from acute (96h) and chronic (28 days) exposure to two antibiotics, oxytetracycline (0, 0.3125, 0.625, 1.25, 2.5 and 5 μgL-1) and ciprofloxacin (0, 0.005, 0.013, 0.031, 0.078 and 0.195 mgL-1) and their mixture (0, 0.005 mgL-1 CIP + 0. 3125 μgL-1 OTC, 0.031 mgL-1 CIP + 1.25 μgL-1 OTC, and 0.195 mgL-1 + 5 μgL-1) in mussels, Mytilus spp. The selected concentrations implemented in both exposure types were defined based on values found in the aquatic environment and are therefore ecologically relevant. The analysis of toxicological effects was carried out by evaluating several parameters of oxidative stress (activities of the enzymes superoxide dismutase and catalase), biotransformation (activity of the isoenzymes glutathione S-transferases) and lipid peroxidation (levels of thiobarbituric acid reactive substances). These parameters were evaluated in three tissues, the gills, the digestive gland, and the muscle. A genotoxicity parameter was also evaluated by the comet assay in the haemolymph and finally a parameter to evaluate the influence of the drugs on the shell hardness of the exposed organisms. In the case of oxytetracycline, this antibiotic caused oxidative damage in the gills of organisms exposed for 28 days at the four highest concentrations (0.625, 1.25, 2.5, and 5 μgL-1). With regard to the genotoxicity biomarkers, an increase in genotoxic damage could be observed with increasing concentrations for both acute and chronic exposure. However, for the biomarker of shell hardness, no effects were observed after exposure to this antibiotic, but a decreasing trend in shell hardness is noteworthy for chronic exposure to oxytetracycline. Exposure to ciprofloxacin resulted in oxidative damage for the three highest concentrations (0.031, 0.078 and 0.195 mgL-1), in the digestive gland of mussels exposed for 28 days to this antibiotic. Acute and chronic exposure to this antibiotic was able to induce genotoxicity in the exposed organisms, with an increase characterized by an increasing dose-response pattern for both exposures. For the parameter of shell hardness, no changes were recorded in the exposed organisms regardless of the exposure time. The mixture of the two antibiotics was made taking into consideration concentrations causing effects in the isolated exposures, however for none of the exposures was it possible to observe oxidative damage despite changes in antioxidant defences. However, the mixture of these two antibiotics was shown to be capable of causing genotoxic damage for both the acute and chronic exposures, and an increase in damage could be observed with increasing concentration of the mixture. Again, for the shell hardness parameter no change was observed after both exposures. This set of data allows us to infer and reinforce the need to evaluate the effects that these compounds may have on non-target organisms. Both antibiotics were shown to be capable of causing deleterious effects to exposed organisms as well as their mixture. The exposure capable of causing the most deleterious effects was oxytetracycline. However, with the results of all the exposures we can conclude that these drugs induce changes in exposed organisms that can result in consequences for the populations, and that it is of extreme ecological importance to evaluate the impact of these types of substances.